Working Capital Structure and Liquidity Analysis: An Empirical Research of Gujarat Textiles Manufacturing Industry - Manjhi, Rakesh Kumar; Kulkarni, S. R. (Indian Journal of Finance, 2012)
The structure of working capital and liquidity analysis plays a vital role in the process of wealth maximization of shareholders. The firms should, therefore, make wise investment in various components of current assets. Having made an attempt to study the effectiveness of structuring the working capital, the study revealed that the sample companies on an aggregate basis invested most of their funds in inventories, followed by loans and advances and trade receivables. The firms held very insignificant amount of funds in cash and near cash assets. The study also indicated that the variation between current assets turnover and working capital turnover was quite high across the industry. However, the sample companies had good current ratios, which also imply the sound liquidity position of sample companies. The hypothesis testing done through one-way ANOVA revealed that the average current ratios, the average quick ratios, the average ratios of current assets to total assets, the average ratios of current assets to sales, the average current assets turnover ratios and the average working capital turnover ratios of sample companies differ significantly.